Investigation on Fiber Optical Parametric Amplifier (FOPA) Bandwidth using Optisystem - Fatin Nabilah, Mohamad Salleh; Nor Shahida , Mohd Shah; Nurul Nadia , Shamsuddin; Siti Nurul Sharina , Mat Yaacob (Universiti Malaysia Pahang, 2016)
This study discusses about single-pump Fiber Optical Parametric Amplifier (FOPA) bandwidth based on Fourwave Mixing (FWM). The wider bandwidth of the gain spectrum of FOPA is one of promising feature nowadays. We has simulates the FOPA in the Optisystem software and analyze the effects of dispersion, dispersion slope and effective area to the bandwidth. The bandwidth is varies as we varies the value of parameter mention before and the widest bandwidth recorded by is 100 nm.